2021
DOI: 10.1002/acr2.11347
|View full text |Cite
|
Sign up to set email alerts
|

Real‐World Treatment Patterns and Healthcare Costs in Patients with Psoriatic Arthritis Treated with Ixekizumab: A Retrospective Study

Abstract: Objective To describe adherence, persistence, discontinuation, restarting, switching, dosing, and health care costs among patients with psoriatic arthritis (PsA) treated with ixekizumab (IXE). Methods MarketScan administrative claims databases were used to select adults (≥18 years) initiating IXE between January 1, 2016, and June 30, 2019, for this retrospective study (earliest IXE claim = index). Eligible patients had one or more PsA diagnoses during the 12 months preceding the index and had 12 months of foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(39 reference statements)
3
6
1
Order By: Relevance
“…Over 50% of IXE patients were bionaïve, and almost 30% took IL inhibitors before the initiation of ixekizumab therapy. This result is in contrast with the previous finding that found that nearly 90% of IXE patients were bioexperienced [ 35 ], but further research on patients taking IXE should be performed to confirm these data.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Over 50% of IXE patients were bionaïve, and almost 30% took IL inhibitors before the initiation of ixekizumab therapy. This result is in contrast with the previous finding that found that nearly 90% of IXE patients were bioexperienced [ 35 ], but further research on patients taking IXE should be performed to confirm these data.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, in the present study, a focused analysis on IXE patients was performed. The patients' characteristics were comparable to those of another real-world study on the use of IXE in PsA patients among the US population [ 35 ]. In our research, almost 90% of the patients taking IXE had a PSO manifestation, which is in line with findings reported by Murage et al [ 35 ] from a study carried out in IXE-treated PsA patients.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…There is limited RWE assessing IXE in PsA patients available in the literature to put our results in context. Two studies conducted in the United States assessed the sociodemographic characteristics, treatment patterns, and IXE persistence in PsA patients included in two claims databases (MarketScan administrative claims and Truven Databases) [ 15 , 16 ]. At the European level, the main evidence comes from two Italian and one Spanish study.…”
Section: Discussionmentioning
confidence: 99%